The Halls Creek Community Families Program: Elements of the role of the child health nurse in development of a remote Aboriginal home visiting peer support program for families in the early years - Munns, Ailsa; Walker, R. (2015)
Objective: To undertake an evaluation of elements of the role of the child health nurse in the development of peer support for Aboriginal families with young children in a remote setting. Design: The Halls Creek Community Families Program uses expertise of peer support workers to support parents of young families. In stage one, participatory action research was used. The program facilitator, who was a child health nurse, undertook action learning sets where issues were explored relating to home visiting strategies to families. Additionally, the facilitator maintained a reflective practice diary. Outcomes contributed to stage two, where an independent researcher evaluated program changes. This report relates to stage one, which used descriptive qualitative data from interviews with peer support workers and community support agencies, and the facilitator's reflective diary. Data were analysed by thematic analysis, focusing on elements of the role of the facilitator in program development. Setting: A remote Aboriginal community in the Kimberley region of Western Australia. Participants: Eight peer support workers and five health and welfare professionals from community support agencies. Main outcome measures: This study measures changes in participants' understanding of the role and scope of practice of the child health nurse facilitator, thereby supporting improved support for Aboriginal families with young children. Results: Thematic analysis identified three major changes in understanding the child health nurse facilitator role: working in partnership, communication strategies and education and organisational strategies.